Longitudinal Changes of Input Impedance, Pulse Wave Velocity, and Wave Reflection in a Middle-Aged Population: The Asklepios Study - Campos-Arias, Daime; De Buyzere, Marc L; Chirinos, Julio A; Rietzschel, Ernst R; Segers, Patrick (Hypertension (Dallas, Tex. 1979), 2021)
[Figure: see text].